Telitacicept: A New Therapy for the Treatment of Optic Neuromyelitis Spectrum Disease Associated with Other Autoimmune Disorders - Zuo S; Yang W; Zhang S; Sun S; Lu S; Lu C; Li W (Biologics: Targets & Therapy)
Shaomin Zuo,1 Wenning Yang,1 Siyu Zhang,2 Shuyue Sun,2 Songke Lu,2 Chengcheng Lu,1 Wei Li3 1Department of Neurology, People’s Hospital of Henan University, Zhengzhou, People’s Republic of China; 2Department of Neurology, People’s Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 3Department of Neurology, Henan Provincial People’s Hospital, Zhengzhou, People’s Republic of ChinaCorrespondence: Wei Li, Department of Neurology, Henan Provincial People’s Hospital, Zhengzhou, People’s Republic of China, Email liwei71@126.comAbstract: Neuromyelitis optica spectrum disorders (NMOSD) are primarily autoimmune diseases mediated by B cells and AQP4-IgG antibodies, typically affecting the optic nerves and spinal cord, and are characterised by high relapse rates and significant disability. We present two cases of NMOSD patients who also had systemic lupus erythematosus (SLE), with one case additionally complicated by myasthenia gravis (MG). Both patients initially received first-line treatment with corticosteroids; however, no clinical improvement was observed; As a result, the treatment was switched to the dual-target biologic agent, Telitacicept. Following the administration of Telitacicept, both patients demonstrated significant improvements in clinical symptoms, daily functional abilities, and imaging findings. This report highlights the successful use of Telitacicept in treating NMOSD complicated by other autoimmune diseases, which may serve as an important reference for the management of NMOSD.Keywords: neuromyelitis optica spectrum disorders, Telitacicept, BLyS, APRIL